Strategic Intelligence Analysis on the Urgency of Establishing a Cyber Force in Indonesia - Suwandi, Suwandi; Suhardi, Suhardi; Prasetiyono, Budi; Surjatmodjo, Dwi; Legowo, Yanuar Adi (Dinasti Research, 2026)
This article examines the urgency of establishing an Indonesian Cyber Force from a strategic intelligence perspective. Cyber threats against national strategic infrastructure continue to escalate, as reflected in billions of detected cyber traffic anomalies in 2025 and the hacking of the Temporary National Data Center (PDNS) in 2024. This study aims to analyze the institutional, regulatory, and cyber defense capacity gaps Indonesia faces amid increasingly asymmetric and difficult-to-attribute threats. A descriptive-analytical qualitative method with a normative-empirical orientation was applied through policy document analysis, statutory review, and in-depth interviews with expert informants in intelligence, defense, and cybersecurity. The results indicate a strategic gap between the escalation of multidimensional cyber threats and the current institutional readiness of Indonesia's defense. The study concludes that establishing a Cyber Force is a logical consequence of the shifting non-conventional threat paradigm. The primary recommendation is a phased approach starting from the consolidation of a unified cyber command to the evolution into an independent fourth branch within the Indonesian National Armed Forces to ensure digital sovereignty and adaptive national resilience.